2000
DOI: 10.1103/physrevb.62.15337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface roughness and alloy disorder on the density of states in semiconductor quantum wires

Abstract: We calculate the effects of surface roughness and alloy disorder on the density of states ͑DOS͒ in cylindrical semiconductor quantum wires with inclusion of a Hubbard local-field correction. It is found that the disorderinduced DOS tail becomes much larger and much more extended below the subband edge when reducing the wire size. Further, the DOS tail at low energies may be enhanced by the Hubbard correction by up to several orders of magnitude. A possibility of applying our results to describe the observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The disorder induced tail of localized states of the exciton center of mass (lying below the ground state of the ideal 1D exciton) gives rise to the observed broadening of the exciton lines. Analysis of the disorder arising from surface roughness and alloy disorder [22] allows us to conclude that the changes of DOS of the 1DEG in a wire reduce to a tail of localized states far below the subband edge.…”
Section: Introductionmentioning
confidence: 99%
“…The disorder induced tail of localized states of the exciton center of mass (lying below the ground state of the ideal 1D exciton) gives rise to the observed broadening of the exciton lines. Analysis of the disorder arising from surface roughness and alloy disorder [22] allows us to conclude that the changes of DOS of the 1DEG in a wire reduce to a tail of localized states far below the subband edge.…”
Section: Introductionmentioning
confidence: 99%
“…Quang and Tung [21] have confirmed that the thinner the wire, the stronger the disorder effect is. The tail of the density of states due to surface roughness overwhelms that due to alloy disorder when the wire radius is much smaller than the effective Bohr radius.…”
Section: Theoretical Modelmentioning
confidence: 58%